Designing A Low-Cost Surface Plasmon Resonance (SPR) Instrument For Monitoring Degradation Of Milk Quality. (August 2019) - Purwalaksana, A Z; Suendo, V; Yuliarto, B; Hendro,
Abstract: A design of a low-cost SPR instrument has been made to monitor the degradation of milk quality. The cost-production of the SPR instruments is much more economical, namely around IDR 10, 000, 000 where the price of commercial SPR instruments such as nanoSPR6 is 9, 950. The main components of the instrument are consist of an Arduino Uno microcontroller, red laser, polarizer, stepper motor, prism, gold chip, and a cell phone camera. The light detection system of the instruments is using image processing that utilizes recorded data from the cell phone camera programmed with python software. The sample in this research used is pasteurized milk. The measurement results obtained from the SPR instruments are compared with nanoSPR6. The sensorgram result from the monitoring of pasteurized milk using both SPR instruments for 12 hours and nanoSPR6 for 4 hours has experienced a decrease in light intensity. The light intensity had decreased up to 8 hours from the time of observation and remained flat for the next 4 hours. This decreased intensity states that there is a shift in the angle dip during the monitoring process. This explanation is supported by track mode measurement data by nanoSPR6 that run for 2 hours, showing a change in the angle dip from 67.34° to 67.6°. The increase in angle dip during the monitoring process is because of increasement in the dielectric constant and the density of the milk during the process of quality degradation. In addition, it is also suspected to be due to the appearance of fatty deposits in milk which results in an increase in the milk refractive index. The change of the milk refractive index within 2 hours is 0.0023 obtained by a fitting process using the Winspall software.